Evaluation of the IEEE 802.11p-based TDMA MAC method for road side-to-vehicle communications - Saeed, Rashid Abdelhaleem; Naemat, Amran; Aris, Azrin; Awang, Mat Khamis @ Mat Kamil (INTI University College, 2010)
Wireless vehicular communications (WVC) has been identified as a key technology for intelligent transportation systems (ITS) for a few years ago. IEEE 802.11p is the proposed standard for physical and MAC layer of WVC devices. The main objective of the standard is to change the frame format and increase delay spread tolerance introduced by vehicle mobility, in which the channel bandwidth is scaled from 20 MHz i.e.802.11a to 10 MHz i.e. 802.11p. This paper proposes TDMA technique with fixed time slots and guard band between slots to ensure interoperability between wireless devices communicate in rapidly changing environment where transactions must be completed in small timeframe. The new TDMA sub-layer is proposed to be on-top of the conventional 802.11p MAC. The simulation results present the performance analysis and validate the efficiency of the proposed scheme.